Application of machine learning in identification of best teaching method for children with autism spectrum disorder - Zoana, Zarin Tassnim; Akter, Nasrin; Shafeen, Mahmudul Wahed (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.